GENERIC MEDICINES, PATENTING OF PHARMACEUTICAL INVENTION AND ACCESS TO MEDICINE IN INDIA: A CRITIQUE - Srivastava, S.P. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the pharmaceutical industry, firms normally invest hundreds of millions of dollars in R & D and clinical trials on their drugs before it is sold in the market, while their generic medicine rivals are exempted from those requirements and enter the market at low cost with nominal investments. Developed countries medicine companies argue why generic drugs manufacturer should be permitted to reap fruits of patented medicine. However, generic drug manufacturers are of the opinion that big pharmaceutical houses are indulged in unfair practice and they are trying to get extra duration through evergreening patent. The basic formula of the compound is already known, and persons with ordinary skill and knowledge in the art can easily obtain the new crystalline form through general and routine operations. Hence, there is nothing novel to the development of a new crystalline form; instead, it should be manufacturer as a "discovery" of a natural substance, not as an "invention" that can be protected under patent law. Considering the global importance and political-economic stakes involved thereto this paper is an attempt to find out ways for maintaining balance between the Indian Biotech industry, global economic players and government liability to society.